ANALISIS USER INTERFACE PADA WEBSITE BUKALAPAK DENGAN METODE HEURISTIC - Girdayanto, Teguh Meirizky; Andry, Johanes Fernandes; Limawal, Isabelle Ivana; Debby, Frian; Jubiko, Jubiko (Narada : Jurnal Desain dan Seni, 2022)
Human and computer interaction is a science that focused on system planning and design a system so that users can interact and collaborate according to the needs of the users themselves in the most effective way at every step of their work. The role of the user interface has a significant impact on the usability of an application or system. Heuristic evaluation (HE) is considered to be the best usability evaluation method compared to other methods because it can find serious problems that cannot be detected by other methods. Therefore, researchers will analyze the user interface on the Bukalapak website using the HE method. User Interface Analysis on the Website with the HE Method through the distribution of online questionnaires, from the results of distributing questionnaires online, it can be concluded that the website has shortcomings in terms of helping and documentation features to assist users in using the system. It is declared lacking because it has the lowest rcount (Total) value of 0.587 compared to other rcount. Suggestions for research on user satisfaction analysis using the HE method, authors convey suggestions that need to be improved in future research, namely it is necessary to conduct research on Bukalapak user satisfaction using the HE method in a wider scope.